Diseño de un plan estratégico de marketing para el posicionamiento de la asociación de productores y productoras nueva esperanza en el mercado del cantón Salcedo, provincia de Cotopaxi, periodo 2014 – 2017 - Iza Cadena, Sandra Elizabeth (2015)
The present investigation work was carried out in order to make a strategic marketing plan for the producer’s association “Nueva Esperanza” of Mulalillo parish.Through this work of markets, it researched a variety of important information for both researchers and the association,; between them, it determined tastes, desires, needs and consumers’ preferences with respect to the products’ consumption derived from grains and vegetables. After having completed market research, we proceeded to make the proposal for the association, where various parameters to be taken into account to improve their competitive advantage and market positioning is established….